Use of hospital services by homeless families in an inner London health district. Issue 6701 (16th September 1989) - Victor, C. R.; Connelly, J.; Roderick, P.; Cohen, C.
Abstract : Over the past decade the number of families in London who were considered officially to be homeless appreciably increased. In response to this many families have been given temporary accommodation, usually in bed and breakfast hotels, while awaiting permanent rehousing. About 200 of the roughly 600 hotels in London that provide such accommodation are located in the area of the former Paddington and North Kensington Health Authority, now part of Parkside Health Authority. The use made by the homeless population of hospital services was studied by finding out the numbers of inpatients admitted to hospital and the numbers presenting to the walk in paediatric clinic and the casualty department at one hospital. These figures were compared with those for local residents and the overall workload. The bed and breakfast population were high users of inpatient beds, the casualty department, and the paediatric clinic. Overall, about one tenth of the beds were used by these people. The health authority receives no additional funding for this group of patients. Further research is needed to find out if the high use of hospital services made by these patients reflects their increased morbidity or their inability to obtain primary care services.